1994
DOI: 10.1016/s0950-821x(05)80448-7
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress influences the release of platelet derived growth factor and basic fibroblast growth factor by arterial smooth muscle cells

Abstract: Increasing shear stress promotes the release of both PDGF and bFGF from arterial SMC in culture and is a possible explanation for atherosclerosis formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Affinity modulation of FGFRs has been shown to occur in cultured vascular SMCs. 25 A previous study 26 has shown that shear stress can influence the release of growth factors, such as FGF-2 and platelet-derived growth factor, which is in agreement with our results. However, that study did not consider the possibility of cell loss or detachment on flow (which apparently occurred in their system) as the source of released FGF-2.…”
Section: Discussionsupporting
confidence: 93%
“…Affinity modulation of FGFRs has been shown to occur in cultured vascular SMCs. 25 A previous study 26 has shown that shear stress can influence the release of growth factors, such as FGF-2 and platelet-derived growth factor, which is in agreement with our results. However, that study did not consider the possibility of cell loss or detachment on flow (which apparently occurred in their system) as the source of released FGF-2.…”
Section: Discussionsupporting
confidence: 93%
“…6 Conversely, relative elevations of blood flow and shear stress appear to have an atheroprotective role and inhibit intimal thickening after vascular injury. [7][8][9] Hemodynamic forces have been shown to modulate endothelial and vascular smooth muscle cell (VSMC) responses, which involve the induction of cytokines, such as platelet-derived growth factor (PDGF), basic fibroblast growth factor, and transforming growth factor-␤1 (TGF-␤1), 10,11 in addition to other mediators, such as nitric oxide, 7 tissue plasminogen activator, 12,13 and matrix metalloproteinases (MMPs), 1 4 involved in vascular remodeling.…”
mentioning
confidence: 99%
“…[8][9][10]21,23) bFGF production increases under certain pathological conditions 9) and may prevent neuronal injury. A number of studies have shown the protective effect of bFGF in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the level of bFGF in bovine aortic SMCs is proportional to the amount of shear stress applied to endothelial cells, suggesting that a hemodynamic factor is a possible regulator of bFGF synthesis. 21) If this relationship was to exist in cerebral arterioles, vascular bFGF production may regulate rCBF in conjunction with hemodynamic conditions. Extraluminal application of bFGF caused vasodilation accompanied by membrane hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%